372 Small italian enterprises and their effective application of laws concerning occupational health: a six years study. (24th April 2018) - D'Orso, Marco Italo; Riva, Michele Augusto; Fabretto, Piatrizia; Messa, Alessandra; Colais, Letizia; Cesana, Giancarlo
Abstract : Introduction: Small enterprises are the majority of productive activities in Italy. For a small enterprise activation of regulations prescribed by European law concerning occupational health promotion is difficult and proportionally expensive. This fact could originate a delay in application of preventative laws comparing with what usually happens in bigger firms. Methods: State of application of laws concerning occupational health and safety in Italy has been evaluated a first time in 2011 in 1458 small enterprises (less than 50 workers). Evaluation has been repeated in 2017 in same firms to verify the possible differences in application of laws carried out in this six years period. For every enterprise we verified presence of a regular program of occupational medicine carried out by an Occupational Health Doctor according to guidelines of Italian Occupational Health Association. We also evaluated Occupational Doctors' role in risk assessment. We evaluated adoption of correct personal protective devices, their use and specific individual formation programs. We also studied legal problems eventually found in small firms carrying out these programs. Results: Only in 21.8% of firms evaluated we evidenced complete and adequate applications of laws. In 81.9% firms correct occupational health programs were regularly carried out. Occupational Health Doctors have been involved in risk assessment in 71, 8% firms. Personal protective devices were adopted and used only in 55, 4% firms. Specific individual formation programs for workers were carried out in 48, 5% firms. We present data divided for different productive sectors comparing them with data collected in 2011. Discussion: Small enterprises respect of laws concerning workers' health and safety is increased comparing with what resulted in 2011 but it is still not satisfactory. A more active Occupational Health Doctors role could increase workers' safety and health in these firms. This result could be obtained only increasing employers' and employees' cultural specific level.